UN PEACEKEEPING: MAIN DIRECTIONS OF EVOLUTION - Lyamzin Andrei; Elantseva Natal’ya; Nikolaev Yurii (Электронное приложение к Российскому юридическому журналу)
The paper analyzes UN peacekeeping operations – peacekeeping missions and identifies problems and contradictions in the peacekeeping activities of the largest international political institution for the 70-year period.